The development and validation of HRIS implementation scale - Butt, Muhammad Farooq Tariq (2020)
Computerized human resource information systems (HRIS) is an innovation in human resource management (HRM) that has been adopted by many organizations to increase HRM effectiveness and enhance organizational communication. However, in Pakistan, the adoption of HRIS is still rather limited. In order to understand the issue of HRIS adoption, the Diffusion of Innovation (DOI) theory explains the process of innovation adoption. Nevertheless, most of the previous studies conducted on HRIS adoption stopped at the decision stage (third stage) of the adoption process, whereby a dichotomous scale of ‘yes’ and ‘No’ was used. Organizations could not get the benefits of HRIS at the decision stage; hence HRIS adoption should be measured at the implementation stage (fourth stage). Unfortunately, previous studies have not studied HRIS adoption at the implementation stage and thus, a scale for measuring HRIS adoption at the implementation stage has to be developed. Using a qualitative research method, the first phase of this study developed a new scale of HRIS adoption at the implementation stage. The qualitative data were collected in July, August, and September of 2016. Data was collected through interviews from the experts of IS and HR in Pakistan. The new scale is unidimensional with ten items. The second phase applied a quantitative research method to test and validate the scale and at the same time, examine the research framework which was established based on the theory of DOI and technology-organization-environment (TOE) framework. Second phase mainly tested the relationship between technological (IT infrastructure, IT expertise), organizational (Top management support, HRM practices, financial readiness), environmental (competitive pressure) factors and HRIS implementation. The data were collected from listed organizations in Pakistan Stock Exchange (PSX). A total of 250 questionnaires were distributed, to HR managers of the organizations, using a systematic random sampling technique and 173 were returned. This study used SPSS V23 and smart PLS 3 for data analysis. This study found IT infrastructure, IT expertise, financial readiness, and top management support (TMS) have a significant positive effect on HRIS adoption. On the other hand, HR practices and competitive pressure have no significant effect on HRIS implementation. The overall reliability of HRIS implementation as measured using Cronbach’s alpha was 0.92. This study provides a few theoretical and practical contributions. First, how to measure HRIS implementation in organizations. The main contribution of this study is the development of HRIS implementations scale. It can be used by researchers to examine relationships with other important factors, explained by TOE framework, that can affect the implementation of HRIS in the organizations. This scale will also provide the bases for researchers in other IS based studies at implementation stage.